Indications for Percutaneous Ultrasound-Guided Renal Biopsy and Complications Associated with it: An Observational Study - Mohammad Ashraf Bhat; Shahid Sulayman; Manzoor Ahmad Parry; Muzaffar Maqsood Wani; Imtiyaz Ahmad Wani (Journal of Renal and Hepatic Disorders)
Renal biopsy is performed for various reasons depending on the clinical manifestations presented. Although percutaneous kidney biopsy is a safe procedure, major or minor complications could occur. Our study aimed to assess the indications for percutaneous renal biopsy and complications associated with the procedure. This was a prospective observational study conducted in the Department of Nephrology, Sher-i-Kashmir Institute of Medical Sciences, Srinagar, India. Patients who underwent percutaneous ultrasound-guided renal biopsy at the institute between October 2017 and June 2019 were enrolled in the study. Data regarding indications for performing a percutaneous renal biopsy and incidence of minor and major post-biopsy complications were collected. A total of 229 patients who underwent ultrasound-guided percutaneous renal biopsy were enrolled in the study. The most common indications for ultrasound-guided percutaneous renal biopsy were nephrotic syndrome (33.3%), subnephrotic proteinuria with azotemia (14%), and unexplained azotemia with proteinuria and hematuria (13.5%). Post-biopsy complications were observed in 89 (37.55%) patients. Minor complications developed in 83 (36.22%) patients and major complications in six (2.62%) patients. Among patients with major complications, two (0.87%) patients underwent invasive procedures (embolization and cystoscopic removal of bladder clot) and four patients developed hemodynamic instability. No procedure-related mortality was reported in the study. The most common indications for renal biopsy were nephrotic syndrome, subnephrotic proteinuria with azotemia, unexplained azotemia with proteinuria, and hematuria. The incidence of major complications was low.